2022
DOI: 10.15430/jcp.2022.27.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oral Microbiota in Carcinogenesis: A Short Review

Abstract: A strong and healthy microbiome is responsible for homeostasis between the host and microbiota which is necessary to achieve the normal functioning of the body. Dysbiosis provokes prevalence of pathogenic microbes, leading to alterations in gene expression profiles and metabolic processes. This in turn results in anomalous immune responses of the host. Dysbiosis may be associated with a wide variety of diseases like irritable bowel syndrome, coeliac disease, allergic conditions, bronchitis, asthma, heart disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 49 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…As research studies have confirmed the prevalence of Fusobacterium genera in the human breast cancer microbial community (Issrani et al., 2022; Tzeng et al., 2021), a growing awareness is whether F. nucleatum accelerates breast tumor progression through immunomodulation and other mechanisms as in colon cancer. Parhi et al.…”
Section: Fusobacterium Nucleatum Is Associated With Breast Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…As research studies have confirmed the prevalence of Fusobacterium genera in the human breast cancer microbial community (Issrani et al., 2022; Tzeng et al., 2021), a growing awareness is whether F. nucleatum accelerates breast tumor progression through immunomodulation and other mechanisms as in colon cancer. Parhi et al.…”
Section: Fusobacterium Nucleatum Is Associated With Breast Cancermentioning
confidence: 99%
“…A supporting analysis by Tzeng et al (2021) reported that Porphyromonas and Fusobacterium accounted for higher proportion in breast cancers with higher tumor stage. Issrani et al (2022) summarized that breast cancers were correlated with Porphyromonas gingivalis, Tannerella forsythia, Fusobacterium nucleatum, and Prevotella spp. However, no study has yet elucidated the specific mechanisms of these microorganisms in carcinogenesis.…”
Section: Oral Microbiology and Breast Cancer Epidemiological Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, while the modern world saw a substantial decrease in smoking prevalence, this decrease did not lead to a decline in oral cancer occurrence [ 84 , 85 ]. Thus, other factors play a significant role in OSCC etiology, including carcinogenic or reactive oxygen species-producing microbiota [ 86 ].…”
Section: Oral Carcinomamentioning
confidence: 99%